Efeito da lidocaína ou lidocaína associada ao meloxicam em cordeiros submetidos a caudectomia por tesoura elétrica - Dallmann, Jeanette María Irene Filippi (2022)
The association of analgesics can improve the response to acute pain in lambs after a surgical procedure. This study aimed to evaluate the effects of the use of lidocaine in comparison with the association of lidocaine + meloxicam in the reduction of pain manifestations presented in newborn lambs when submitted to tail docking. Thirty animals were divided into three groups: Group GC animals without caudectomy (control); Group GL animals submitted to caudectomy and lidocaine and Group GLM animals submitted to caudectomy and lidocaine+meloxicam. The assessment of acute pain in sheep was performed by measuring physiological parameters and a behavioral scale. Respiratory and heart rates and rectal temperature were measured at moments -24 (before the experiment) and 1, 4, 12 and 24 hours after the tail docking. Behavioral assessments were performed at the same moments studied. Weighings were performed at 8, 30 and 60 days of birth. There was no difference in any physiological variable studied or in the average daily weight gain between the groups. Within the moments, higher respiratory rate values were observed at 1h, 4h and 24h in all groups. Higher values of body temperature were observed at 24h in all groups. The animals submitted to caudectomy showed less interaction with the environment, less activity, alteration in posture, greater attention to the surgical wound site, greater miscellany of behaviors in relation to animals from the non-caudectomized lambs group. We conclude that lidocaine or the association of lidocaine and meloxicam did not alleviate pain/discomfort in lambs submitted to electric scissor tail docking.